Scalable Wireless Video Streaming over Real-Time Publish Subscribe Protocol (RTPS) - Al-Madani, Basem; Al-Saeedi, Mohammed; Al-Roubaiey, Anas A. (2013 IEEE/ACM 17th International Symposium on Distributed Simulation and Real Time Applications, 2013)
Enabling Real-Time video streaming over wireless networks faces challenges of time-varying channel conditions and the limited network resources. The instability of wireless networks lead to problems such as limited and time-varying bandwidth and traffic congestion when transmitting a burst of video streams. The time-varying wireless channel conditions expose the transmitted video packets to be delayed or dropped. However, in Real-Time video streaming each frame must be delivered and decoded by its playback time. As a result, efficient Real-Time video streaming requires an efficient video quality of service (QoS) transmission control mechanism to adapt to the network changes. Recently, layer coding (LC) enables Real-Time and scalable video streaming to clients of heterogeneous capabilities by dropping upper enhancement layers without the need of re-encoding and with less bit rate. However, layer coding still facing unfair layer protection problem in which packets from the base or lower layers might be dropped while there is a chance to drop packets from the upper enhancement layers. Loosing packets from the base layer can significantly affect the delivered video quality and sometimes lead to an interruption especially in error-prone networks as wireless networks. Architectural solutions at the middleware level introduce higher flexibility, more efficiency in development time and more QoS control. In this paper, we investigate the behavior of video streaming over Real-Time publish-subscribe based middleware. We propose and develop an unequal layer protection mechanism for Real-Time video streaming based on the Data Distribution Service (DDS) middleware, and show the performance of our approach over IEEE 802.11g WLAN networks. Our approach shows a graceful degradation of video quality while maintaining a robust video streaming free of visible error or interruptions.